El arte de curar. Un paso más The art of healing. One step further - Alberto Bustamante (Asociación Odontológica Argentina, 2013)
Resumen La relación médico-paciente -cincuenta años atrás, armónica y adecuada para ambos- ha cambiado. Tanto en medicina como en odontología, vivimos una época de disenso y desconfianza, caracterizada por los juicios de mala praxis. En este trabajo se esbozan algunas pautas para la recomposición del diálogo perdido. Palabras clave: Relación médico-paciente. Abstract The relationship between doctors and patients, that during the last fifty years was harmonic and adequate for both of them, has changed. We live in medicine and dentistry a moment of dissent and mistrust characterized by malpractice claims. In this paper some guidelines to reinstall the dialogue that has been lost are outlined. Key words: Doctor-patient relationship.